The Effectiveness of Micro-Enterprises In Enhancing The Economic Welfare of Communities - Ilmi Albadiah; Siti Mudawanah; Ade Sahruroji (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2023)
The micro-business of donut production plays a role in alleviating community welfare issues and reducing unemployment rates in the area. It also fosters creativity that aligns with efforts to preserve and develop elements of the local culture. On another note, micro-enterprises like these are capable of absorbing labor, thus decreasing unemployment levels. The effectiveness of the Mawar Donut micro-business in enhancing economic welfare is under scrutiny. To determine how effective the Mawar Donut micro-enterprise is in improving economic welfare, qualitative research is conducted. This research aims to describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions, and thoughts of individuals or groups through qualitative data with a case study approach. Data collection techniques include observation, interviews, and documentation. In this research, documentation refers to the process of collecting data by studying and noting important parts from official records found in both the research location and other influential institutions. This is because the data obtained consists of descriptions or information from interview activities. The findings at Mawar Donut indicate that interviews with Mrs. Ulfah Khofifah, the owner of Mawar Donut store, show effective results regarding the improvement of community welfare around the store. With its strategic location near schools among other areas, Mawar Donut not only enhances its own prosperity but also supports the general economy of the community. Therefore, Mawar Donut has become a business model that caters to all its customers' needs, whether for resale or daily consumption.